Health related quality of life among people with mental illness: The role of socio-clinical characteristics and level of functional disability - Semira Defar; Yacob Abraham; Yared Reta; Bedilu Deribe; Meskerem Jisso; Tomas Yeheyis; Kurabachew Mengistu Kebede; Bereket Beyene; Mohammed Ayalew (Frontiers Media S.A., 2023)
BackgroundPeople with mental illness (PWMI) have declining health related quality of life (HRQoL), which is frequently equivalent to or greater than that of medical disorders. Although, HRQoL is rapidly being recognized as an essential treatment outcome indicator in modern psychiatry, research on the identification and significance of factors impacting QoL in PWMI is still in its early stages.ObjectiveThe aim of this study was to identify predictors of HRQoL among people with mental illness who underwent outpatient follow-up in Sidama region, southern Ethiopia.MethodsWe conducted a multicenter, cross-sectional study from April-1, to May-30, 2022. A total of 412 participants took part in the study, using an interviewer-administered structured questionnaire. The HRQoL was measured using the 12-item Short-Form Health Survey-Version 2 (SF-12v2) scale. To describe different variables, descriptive statistics were employed. To find independent HRQoL predictors, we used multivariable linear regression analysis. P-value of <0.05 were declared statistically significant at 95% confidence interval (CI).ResultOut of 412 participants, nearly two-third 261 (63.3%) were male and nearly half 203 (49.3%) were diagnosed as schizophrenia. HRQoL was positively associated with social support (β = 0.321) and being single (β = 2.680). Conversely, functional disability (β = −0.545), being a student (β = −4.645) and jobless (β = −3.279) by occupation, and being diagnosed with depression (β = −2.839) were negatively impacted HRQoL among PWMI.ConclusionHRQoL of people with mental disorders in this study was significantly associated to social support, marital status, occupation, diagnosis and level of functional disability. Therefore, the mental health care system should develop HRQoL promoting measures that enhance PWMI functioning, social support and employment.